EXPERIMENTAL STUDY OF THE EFFECT OF PLATE CURVES ON SOLAR STOVE - Lohdy Diana; Arrad Ghani Safitra; Agung Dwi Cahyo (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
In the midst of various other energy needs, cooking has received special attention in energy consumption due to the scarcity of fuel for cooking which is currently commonly used by the community. The scarcity is directly proportional to the increase in fuel prices. Currently, many alternative energies are being developed, one of which is cooking using solar power. In this study, an experimental study of the effect of the number of plate bends on the solar cooker carried out. This study aims to determine the effect of the number of curvatures of the plate on the performance of a solar cooker. The number of curved aluminum plates in the solar cooker was expected to be able to expand the area of absorption of solar heat, thereby increasing the temperature of the air inside the solar cooker. The solar cooker also adds an absorbent plate in the shape of a flower-like arc. Variations in the number of arches to be studied are 6, 8, and 12 arches. The method used in this study is an experiment in actual conditions. Research result show solar stoves with 12 curved walls have a higher temperature increase and heat absorption compared to 6 and 8 arches. This is because 12 arches have a wider solar heat absorption area.